4(x-2)=-2x+16

Simple and best practice solution for 4(x-2)=-2x+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-2)=-2x+16 equation:



4(x-2)=-2x+16
We move all terms to the left:
4(x-2)-(-2x+16)=0
We multiply parentheses
4x-(-2x+16)-8=0
We get rid of parentheses
4x+2x-16-8=0
We add all the numbers together, and all the variables
6x-24=0
We move all terms containing x to the left, all other terms to the right
6x=24
x=24/6
x=4

See similar equations:

| −5r+8r+5= | | 3x2+5x+1=0 | | |2x−10|=−3x | | x=245/(x-1) | | 2x2-10x+7=0 | | 7(5+4x)-(3-x)=0 | | N^=18n+40 | | x^2+42x+6=0 | | 3x+7=−x−1 | | (7x-7)/(9x-8)=10 | | 1/x+4-3/x-3=11/4 | | 7y+9-0.5y-10=2y+0.25+6y-7 | | 0.25x2/5= | | 17x^2-68x+289=0 | | x/2+70=100 | | x(x-1)=245 | | 7x-4=8x-8 | | 2/3(9x+6)=6x+4 | | x2+8x-5=0 | | 10x-8/3-4x=6x+9 | | 7x+75=2x | | x/2+70=10 | | 7x+5-x+3=9x-15+3x+5 | | 6x-71=55 | | 2/5(x-3)+1=3 | | x2-6x+6=0 | | 9t-48-4t+16=6t-18-5t-19+5 | | x+19/30=5/6 | | 6x-71=65 | | -10x+10x-15-15=8 | | 0=-14+(m-10) | | -6z-4-3=-29 |

Equations solver categories